EKSISTENSI PEMANFAATAN PENGGUNAAN FITUR S-PINJAM PADA MARKETPLACE SHOPEE DILIHAT DARI ASPEK PERILAKU KONSUMEN DAN HUKUM - Ozzy Kurnia Kurnia; Luqmanul Hakim; Fauzi Yati (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
Technological developments have had a major impact on online-based fund lending services, so that many online lending platforms have emerged that are combined in one marketplace, such as the s-borrow feature. Behind the convenience and practicality offered, not a few consumers use this online loan product unwisely, even though these online loans contain high interest rates but are loved by consumers. The purpose of this study is to determine the behavioral tendencies of marketplace shopee consumers on the s-borrow feature, to determine the factors that influence the behavioral tendencies of the marketplace shopee consumer behavior on the s-borrow feature and to determine the ethics of Islamic consumption behavior on consumer behavior in the marketplace shopee on the s-feature borrow. The data used are primary data and secondary data. The data obtained is processed using data presentation in the form of reduction, display, and verification. The research resulted in the following conclusions. First, the tendency of consumer behavior towards the s-borrow feature is based on fulfillment of needs, convenience, trust, fast disbursement and payment tenor per month. Consumers underlie these loans because there is no quick solution for getting money loans. Second, the factor that influences consumer behavior towards the s-borrow feature is the technology factor. Third, the ethics of Islamic consumption behavior towards marketplace shopee consumer behavior on the s-borrow feature includes israf and tabzir behavior, the law of its use is makruh.